2001
DOI: 10.1152/ajpheart.2001.281.5.h2028
|View full text |Cite
|
Sign up to set email alerts
|

Gender affects sympathetic and hemodynamic response to postural stress

Abstract: We tested the hypothesis that differences in sympathetic reflex responses to head-up tilt (HUT) between males (n = 9) and females (n = 8) were associated with decrements in postural vasomotor responses in women. Muscle sympathetic nerve activity (MSNA; microneurography), heart rate, stroke volume (SV; Doppler), and blood pressure (Finapres) were measured during a progressive HUT protocol (5 min at each of supine, 20 degrees, 40 degrees, and 60 degrees ). MSNA and hemodynamic responses were also measured during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
211
9
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(251 citation statements)
references
References 39 publications
26
211
9
5
Order By: Relevance
“…By contrast, information concerning the effects of endogenous and exogenous estrogen on reflex MSNA responses to orthostatic stress is both limited and inconsistent. For example, head-up tilt has been reported to elicit both lower 21 and similar 22 MSNA responses in young women compared with men. Simulated orthostatic stress augments MSNA more during the mid-luteal phase (high estrogen and progesterone) than in the early follicular phase (low estrogen and progesterone) of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, information concerning the effects of endogenous and exogenous estrogen on reflex MSNA responses to orthostatic stress is both limited and inconsistent. For example, head-up tilt has been reported to elicit both lower 21 and similar 22 MSNA responses in young women compared with men. Simulated orthostatic stress augments MSNA more during the mid-luteal phase (high estrogen and progesterone) than in the early follicular phase (low estrogen and progesterone) of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic CPT effect is maximal about 60 s after limb immersion, and most people find it remarkably painful to hold their hand in freezing water for more than 120 s. 1 HR and BP changes following CPT stimulation were not affected by either age or gender. 2 Cerebral blood flow velocity (CBFV) showed variable response to CPT. Some studies found bilateral or unilateral (in the brain hemisphere that is contralateral (Co) to the cold applied hand) CBFV increase during CPT.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 On the other hand, previously reported findings in normotensive populations have not been consistent as to whether MSNA levels are different between men and women. Young women may have a lower [15][16][17][18][19] or similar 20,21 level of resting MSNA relative to young men. Also, older women may have a lower 15 or similar 17,19 level of resting MSNA relative to older men.…”
Section: Introductionmentioning
confidence: 99%